Folliculin, the product of the birt-hogg-dube tumor suppressor gene, interacts with the adherens junction protein p0071 to regulate cell-cell adhesion - Medvetz, Doug A.; Schlechter, Tanja; Hofmann, Ilse (PLOS ONE, 2012)
Birt-Hogg-Dube (BHD) is a tumor suppressor gene syndrome associated with fibrofolliculomas, cystic lung disease, and chromophobe renal cell carcinoma. In seeking to elucidate the pathogenesis of BHD, we discovered a physical interaction between folliculin (FLCN), the protein product of the BHD gene, and p0071, an armadillo repeat containing protein that localizes to the cytoplasm and to adherens junctions. Adherens junctions are one of the three cell-cell junctions that are essential to the establishment and maintenance of the cellular architecture of all epithelial tissues. Surprisingly, we found that downregulation of FLCN leads to increased cell-cell adhesion in functional cell-based assays and disruption of cell polarity in a three-dimensional lumen-forming assay, both of which are phenocopied by downregulation of p0071. These data indicate that the FLCN-p0071 protein complex is a negative regulator of cell-cell adhesion. We also found that FLCN positively regulates RhoA activity and Rho-associated kinase activity, consistent with the only known function of p0071. Finally, to examine the role of Flcn loss on cell-cell adhesion in vivo, we utilized keratin-14 cre-recombinase (K14-cre) to inactivate Flcn in the mouse epidermis. The K14-Cre-Bhdflox/flox mice have striking delays in eyelid opening, wavy fur, hair loss, and epidermal hyperplasia with increased levels of mammalian target of rapamycin complex 1 (mTORC1) activity. These data support a model in which dysregulation of the FLCN-p0071 interaction leads to alterations in cell adhesion, cell polarity, and RhoA signaling, with broad implications for the role of cell-cell adhesion molecules in the pathogenesis of human disease, including emphysema and renal cell carcinoma.